Design and Prototyping of an Underactuated Hand Exoskeleton With Fingers Coupled by a Gear-Based Differential - Dragusanu, Mihai; Troisi, Danilo; Villani, Alberto; Prattichizzo, Domenico; Malvezzi, Monica (Frontiers in Robotics and AI, 2022)
Exoskeletons and more in general wearable mechatronic devices represent a promising opportunity for rehabilitation and assistance to people presenting temporary and/or permanent diseases. However, there are still some limits in the diffusion of robotic technologies for neuro-rehabilitation, notwithstanding their technological developments and evidence of clinical effectiveness. One of the main bottlenecks that constrain the complexity, weight, and costs of exoskeletons is represented by the actuators. This problem is particularly evident in devices designed for the upper limb, and in particular for the hand, in which dimension limits and kinematics complexity are particularly challenging. This paper presents the design and prototyping of a hand finger exoskeleton. In particular, we focus on the design of a gear-based differential mechanism aimed at coupling the motion of two adjacent fingers and limiting the complexity and costs of the system. The exoskeleton is able to actuate flexion/extension motion of the fingers and to apply bi-directional forces, i.e. it is able to both open and close the fingers. The kinematic structure of the finger actuation system has the peculiarity to present 3 DoFs when the exoskeleton is not worn and 1 DoF when it is worn, allowing better adaptability and higher wearability. The design of the gear-based differential is inspired by the mechanism widely employed in the automotive field, it allows to actuate two fingers with one actuator only, keeping their motions independent.